COVID-19 Induced Economic Slowdown and Mental Health Issues - Gong, Yimiao; Liu, Xiaoxing; Zheng, Yongbo; Mei, Huan; Que, Jianyu; Yuan, Kai; Yan, Wei; Shi, Le; Meng, Shiqiu; Bao, Yanping; Lu, Lin (Frontiers in Psychology, 2022)
The COVID-19 pandemic has pressed a pause button on global economic development, and induced significant mental health problems. In order to demonstrate the progressed relationship between the pandemic, economic slowdown, and mental health burden, we overviewed the global-level gross domestic product changes and mental problems variation since the outbreak of COVID-19, and reviewed comprehensively the specific sectors influenced by the pandemic, including international trade, worldwide travel, education system, healthcare system, and individual employment. We hope to provide timely evidence to help with the promotion of policymakers' effective strategies in mitigating economic losses induced by the pandemic; we suggest different governments or policy makers in different countries to share information and experience in dealing with COVID-19-induced economic slowdown and promote COVID-19 vaccine popularization plan to protect every individual worldwide against the coronavirus essentially; and we appeal international information share and collaboration to minimize stigmatization related to adverse mental consequences of COVID-19 and to increase mental health well-beings of people all over the world.